2017
DOI: 10.1007/s00253-017-8654-1
|View full text |Cite
|
Sign up to set email alerts
|

Erythritol as sweetener—wherefrom and whereto?

Abstract: Erythritol is a naturally abundant sweetener gaining more and more importance especially within the food industry. It is widely used as sweetener in calorie-reduced food, candies, or bakery products. In research focusing on sugar alternatives, erythritol is a key issue due to its, compared to other polyols, challenging production. It cannot be chemically synthesized in a commercially worthwhile way resulting in a switch to biotechnological production. In this area, research efforts have been made to improve co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
43
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 91 publications
(63 citation statements)
references
References 49 publications
(63 reference statements)
0
43
0
1
Order By: Relevance
“…EOL synthesis and production strategies in bioreactors have been recently reviewed by our groups and others [97,104,105]. Therefore, only the main achievements that are not covered in these reviews will be presented in this section.…”
Section: Erythritolmentioning
confidence: 99%
“…EOL synthesis and production strategies in bioreactors have been recently reviewed by our groups and others [97,104,105]. Therefore, only the main achievements that are not covered in these reviews will be presented in this section.…”
Section: Erythritolmentioning
confidence: 99%
“…Nevertheless, its production (unlike that of other polyols) is a challenging issue, since it cannot be chemically synthesized in a commercially worthwhile way; therefore, current research efforts are trying to improve both productivity and yield. A short review by Regnat, Mach, and Mach-Aigner [29] gives an overview of the attempts to improve erythritol production, as well as their development over time.…”
Section: Muffinsmentioning
confidence: 99%
“…Erythritol is a four‐carbon polyalcohol with a limited caloric intake (0.2 kcal/g), with a glycemic index equal to zero, making it ideal for diabetic patients or for patients affected by impaired glucose tolerance (Wölnerhanssen et al, ); furthermore, it also had shown a preventing effect on vascular function in patients with type 2 diabetes (Flint et al, ). Its sweetening power has been estimated around 60–80% of the common sucrose; moreover, erythritol does not accumulate in the intestinal lumen, thus limiting the possibility of diarrhea and cramp‐like abdominal pains, instead allowing intestinal absorption and consequent elimination by the renal route (Regnat, Mach, & Mach‐Aigner, ); it does not have the bitter aftertaste typical of other polyalcohols. Erythritol can be produced either by chemical methods (Otey, Sloan, Wilham, & Mehltretter, ) or by biotechnological methods, through fermentation by yeasts and bacteria (Moon, Jeya, Kim, & Lee, ).…”
Section: Introductionmentioning
confidence: 99%